KEPASTIAN HUKUM DALAM PELAYANAN KESEHATAN MELINDUNGI TENAGA MEDIS - Phonna Ridha; Sumarno Sumarno; Marice Simarmata (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The phenomenon of increasing criminalization of medical personnel in various cases in Indonesia raises concerns about legal certainty in the health world. Therefore, it is important to examine how the national legal system provides fair and balanced protection for medical personnel in carrying out their duties. This research uses normative juridical methods, with legislative, conceptual, and case study approaches. The data used includes related laws and regulations, legal literature, and medical professional documents. This approach aims to analyze the legal norms that govern the protection of medical personnel, as well as identify legal gaps or disharmonized norms that have the potential to hinder legal certainty. The results of the study show that although there are a number of regulations such as the Medical Practice Law, the Hospital Law, and the Criminal Code, the implementation of legal protection for medical personnel still faces challenges. Different interpretations of the law by law enforcement officials, as well as patients' ignorance of medical procedures, often cause medical personnel to become vulnerable parties. In addition, the non-optimal role of the Indonesian Medical Discipline Honorary Council (MKDKI) in separating the ethical and criminal realms has also muddy law enforcement in the health sector. In conclusion, legal certainty for medical personnel can only be realized through strengthening regulations that affirm the limits of legal responsibility of medical personnel, as well as the need for alignment between criminal law instruments and professional ethics. Legal education for the community and increased competence of law enforcement officials in understanding the medical context are also needed.  Keywords: Legal certainty, medical personnel, legal protection. Abstrak: Fenomena meningkatnya kriminalisasi tenaga medis dalam berbagai kasus di Indonesia menimbulkan kekhawatiran akan kepastian hukum dalam dunia kesehatan. Oleh karena itu, penting untuk menelaah bagaimana sistem hukum nasional memberikan perlindungan yang adil dan seimbang terhadap tenaga medis dalam menjalankan tugasnya. Penelitian ini menggunakan metode yuridis normatif, dengan pendekatan perundang-undangan, konseptual, dan studi kasus. Data yang digunakan adalah mencakup peraturan perundang-undangan terkait,  literatur hukum, dan dokumen profesional medis. Pendekatan ini bertujuan untuk menganalisis norma hukum yang mengatur perlindungan tenaga medis, serta mengidentifikasi kekosongan hukum atau disharmonisasi norma yang berpotensi menghambat kepastian hukum. Hasil penelitian menunjukkan bahwa walaupun terdapat sejumlah regulasi seperti Undang-Undang Praktik Kedokteran, Undang-Undang Rumah Sakit, dan Kitab Undang-Undang Hukum Pidana, namun implementasi perlindungan hukum terhadap tenaga medis masih menghadapi tantangan. Interpretasi hukum yang berbeda oleh aparat penegak hukum, serta ketidaktahuan pasien terhadap prosedur medis, sering kali menyebabkan tenaga medis menjadi pihak yang rentan. Selain itu, belum optimalnya peran Majelis Kehormatan Disiplin Kedokteran Indonesia (MKDKI) dalam memisahkan ranah etik dan pidana turut memperkeruh penegakan hukum di bidang kesehatan. Sebagai kesimpulan, kepastian hukum bagi tenaga medis hanya dapat terwujud melalui penguatan regulasi yang menegaskan batas tanggung jawab hukum tenaga medis, serta perlunya penyelarasan antara instrumen hukum pidana dan etik profesi. Diperlukan pula edukasi hukum bagi masyarakat dan peningkatan kompetensi aparat penegak hukum dalam memahami konteks medis. Kata kunci: Kepastian Hukum, Tenaga Medis, Perlindungan Hukum.